Seroprevalence of Toxoplasmosis among women with habitual abortion in Thi – Qar Governorate using ELISA test - H. Al-khafaji , Ahmed; I. Muhsen, Kawakib (University of Thi-Qar Journal of Science, 2009)
Venous blood had been collected from seventy four women with habitual abortion from Thi – Qar Governorate cities to evaluate the prevalence of the toxoplasmosis and from fifteen healthy looking women as control. The test performed by using ELISA method to detect the IgM and IgG antibodies in patients sample by commercial kit. The result showed that 30 of 74 women (40.5%) had toxoplasmosis, 13 (43.3%) with IgM antibodies, 7 (23.3%) with IgG antibodies and 10 (33.3%) with both IgM and IgG antibodies. Other women (44) although had habitual abortion but they were negative for toxoplasmosis.